2020
DOI: 10.1088/1742-6596/1700/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Development of computer aided manufacturing learning module for Magelang vocational high school students

Abstract: This study aims to develop computer aided manufacturing (CAM) learning modules for students, find out the feasibility of learning modules for students, and find out student assessments of modules. The research method used is 4D (Define, Design, Develompent, Dissemination). Data collection using a questionnaire. The results showed the feasibility of teaching materials by material experts who get a percentage of 84.17% with a very decent category, from CNC learning practitioners get a percentage of 85.83% with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Canva is the right choice when it comes to creating more interactive modules because of the features it offers. In a study by Rahmatullah et al (2020), Canva is also identified as a graphic design tool that makes it easy to create electronic modules featuring moving animations and adding video links.…”
Section: Introductionmentioning
confidence: 99%
“…Canva is the right choice when it comes to creating more interactive modules because of the features it offers. In a study by Rahmatullah et al (2020), Canva is also identified as a graphic design tool that makes it easy to create electronic modules featuring moving animations and adding video links.…”
Section: Introductionmentioning
confidence: 99%